After the Muktamar: Is a New PAS Emerging? - Yang Razali Kassim (2017)
Malaysia’s Islamist party PAS held its 63rd congress amid huge publicity of a full and complete break from the opposition alliance. The bigger significance, however, is what this all means and what future direction PAS will take.